Gerakan dan pemikiran Muhammadiyah : 18 Nopember 1912 M - Muna, Vicka Naylul (Maliki Interdisciplinary Journal, 2025)
Muhammadiyah is an Islamic movement founded by KH. Ahmad Dahlan in 1912. The aim was to purify the Islamic religion, strengthen pure Islamic teachings, and develop a Muslim community based on the Koran and Hadith. Through da’wah, education and social activities, Muhammadiyah established a moderate and progressive Islamic identity in Indonesia. This movement promotes the values ​​of justice, equality and togetherness, as well as developing social awareness and concern for society. Muhammadiyah contributes to the development of Islamic education, health and social welfare. This movement helps create an Islamic society of faith, knowledge and noble character. With a wide network and various charitable efforts, Muhammadiyah has become one of the largest Islamic organizations in Indonesia. Its role in building a harmonious and just society is very significant. Muhammadiyah continues to contribute to the progress of the Indonesian nation through social activities, da’wah, education and other activities. With a clear vision and mission, Muhammadiyah is ready to face future challenges with optimism and enthusiasm. Muhammadiyah remains committed to moderate and progressive Islamic values.